SPECIAL CHARACTERISTICS OF CHRONIC ADENOIDITIS ASSOCIATED WITH CHLAMYDIA INFECTION - T. A. Kapustina; E. V. Belova (Вопросы современной педиатрии)
Aim: to study clinic-epidemiologic and immunologic characteristics of clinical manifestations of chronic adenoiditis associated with chlamydia infection in children. Patients and methods: 169 children aged from 3 to 15 years old administered to the ENT-department due to inefficacy of out-patient treatment were examined. In order to identify chlamydia structures and specific antibodies direct (polymerase chain reaction, direct immunofluorescence assay) and indirect (immunoenzyme assay) were used. Assessment of the cellular immunity was performed with the method of indirect immunofluorescence assay with monoclonal antibodies. Results: the authors showed a high contamination of the epithelium of pharyngeal mucous membrane with chlamydia infection, described cultural structure of the verified chlamydia and clinical manifestations as well as special characteristics of immune responseп of children with chronic adenoiditis associated with this infection. Conclusions: clinical manifestations of chronic adenoiditis in chlamydia-infected children does not have clear pathognomonic signs; there are special characteristics of immune reactivity in children with verified chlamydia infection, such as more prominent imbalance of T-cell immunity and less intensity of antibody response; association of chlamydia with extracellular bacterial infection aggravates imbalance of the immune system and leads to inhibition of the both forms of the immune response.